Reducing alcohol-related harm and social disorder in a university community: a framework for evaluation. Issue 5 (4th October 2010) - Cousins, Kimberly; Connor, Jennie L; Kypri, Kypros
Abstract : Background: In New Zealand and other middle to high income countries, university student are at high risk of alcohol-related injury and other problems due to their typical pattern of episodic heavy drinking. In 2007, one university implemented Campus Watch, a novel and extensive programme to reduce social disorder, including alcohol-related injury, in the university area. Objectives: To quantify the effects of this complex intervention. Setting: A large public university campus and surrounding community in New Zealand. Design: A health promotion evaluation model was used, examining: (1) how the programme was developed, introduced and received by the community? (process); (2) whether the programme affected behaviour? (impact); and (3) whether the programme reduced social disorder and alcohol-related harm in particular? (outcome). The outcome phase uses a non-equivalent control group design to measure changes occurring in the Campus Watch area compared with other universities, and with a same-city control site. Participants: Programme staff, university students and other community members. Data: Interviews with university administrators and Campus Watch staff; surveys of local residents' views; Campus Watch incident data; national surveys of university students in 2005, 2007 and 2009; police data; fire department data. Outcome Measures: Prevalence of heavy episodic drinking; number of acute alcohol-related harms; incidence of antisocial behaviour, assault and street fires. Analysis: Regression analyses will be used to examine changes in the intervention site relative to changes in the control areas.